PENGEMBANGAN VIDEO ANIMASI UNTUK PEMBELAJARAN DESCRIPTIVE TEXT DALAM MATA PELAJARAN BAHASA INGGRIS - Dwi Juliati Ciptaningsih; Aloysius Mering; Indri Astuti (Universitas Tanjungpura, 2021)
AbstractThe development of animated videos for descriptive text learning in English subjects is classified as the development of audio-visual technology based on the concept of learning technology using instructional design, namely through the planning, production, and evaluation stages. The type of research used in this research was the type of research and development or Research and Development (R&D). The animation video in this study was designed using the ADDIE model. The results showed that from the design expert's judgment, this animated video was declared